Relationship between electromechanical response and percolation threshold in carbon nanotube/poly(vinylidene fluoride) composites - Ferreira, A. (2013)
This paper reports on the piezoresistive response of carbon nanotube/poly(vinylidene fluoride), CNT/PVDF, composites prepared with different CNT types with and without functionalization, via in situ-generated diazonium compounds. The results show that for a CNT concentration close to the percolation threshold, tunneling is the main mechanism responsible for the electrical response, leading also to a significant increase of the piezoresistance of the composites. Interestingly, this fact is independent of the CNT type or functionalization, as well as of the percolation threshold concentration. In this way, a close relationship between the percolation threshold and the piezoresistive response was demonstrated. The electromechanical response, as characterized by the gauge factor, reach values up to 3.9, being among the largest obtained for thermoplastic composites and demonstrating the suitability of these materials for sensor applications.